A scientific review of soft-computing techniques and methods for stock market prediction - R. Islam, Muhammad; F.T. Al-Shaikhli, I; Abdulkadir, A (International Journal of Engineering and Technology, 2018)
Information could be power if most technological approach engaged in the era of IT.Â  Web based text mining is one of the approach that could be analyzed in many ways through soft-computing methods and techniques. The analytical result has shown that different methods of text mining have several advantages with the gap of knowledge that is required to improve. This paper explores the performance of various methods and its impact on specific text mining field such as web based financial text analysis for stock prediction. Key research area of financial text mining is becoming one of the potential research field based on the source of online news, forums, blogs or social media.